Pharmacotherapy of Gastropathy (Literature Review) - Djanaev G.Yu; Khudayberdiev Kh.I; Askarov O.O; Sultanov S.A (Zien Journals, 2023)
Disruption of secretory and movement activity of the gastrointestinal tract is observed in many diseases and pathological conditions. A large arsenal of drugs is used to normalize the functions of the gastrointestinal tract. It mainly contains substances that directly affect the secretory and movement functions of the stomach and intestine, as well as the excretory function of the pancreas and liver. At the same time, they include appetite suppressants, as well as anti-vomiting and anti-vomiting drugs.
Keywords: gastropathy; M-cholinoblockers; Proton pump inhibitors pathogenesis; Misoprostol